Inflation and its Influence on Daily Wage Working Class: A Case Study of Rawalakot AJK - Anwar, Laiba; Ashraf, Mehwish; Hina, Syeda Mahlaqa; Kamran, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This research investigated empirically the influence of inflation on daily wage working class. Inflation is a term used in economics to describe a phenomena in which the prices of goods and services in an economy rise over time. Inflation indicates that, on average, goods get more costly with time. It is calculated as the percentage rise in the overall level of goods and services prices during a specific time period, usually a year. The central focus of the study was to dig out the influence inflation have on daily wage working class. The present study was conducted in Rawalakot Poonch ajk. In the current study, qualitative research methodology has been used. Ten people made up the sample. An interview guide was employed as a means of gathering primary research data. The collected data was examined thematically. The findings show that inflation has a negative impact on daily wage workers. The laborers' backs have been shattered by skyrocketing inflation. The daily wage working class is unable to satisfy their basic living necessities due to growing inflation. Labor earnings have not grown as much as commodity prices have. Along with financial challenges, the working class has suffered from psychological issues throughout this period of inflation. The study has also found when the daily wage workers are unable to meet the needs of the household quarrels and conflicts arise in the household and create a situation of insecurity.